The attitude and perception of various churches and religious leaders of Iloilo City on former President Estrada's governance - Abello, Jill I.; Conanan, Carina Johna Keith T.; Dato, Joselia P.; Imperial, Bernadette S.; Moscoso, Lara Vanessa E. (2001.)
Executive summary - The group conducted this research to know the attitudes and perceptions of various churches and religious leaders on former President's Estrada's governance. The various churches and religious leaders were the main focus of the study for they play an important role in molding the well being of citizens in society. The respondents were taken from various churches and religious organizations in Iloilo City namely : The Roman Catholic ; Protestants, Iglesia ni Cristo, Iglesia Filipina Independente or Philippine Independent Church, Seventh Day Adventist, Church of Jesus Christ of the Latter Day Saints, A postolic Jesus Name Church, Iglesia ng Diyos kay Kristo Jesus, Haligi at Saligan ng Katotohanan (Dating Daan), Iloilo Trinity Church Iloilo Christian Reformed Church and the Universal Catholic Church. The group made use of the survey method. After the presentation of the findings and analysis, the group came up with the conclusion that former President Estrada's governance was indeed poor as perceived by the various inter-denominational leaders. The group recommendations focused more on the various religious organizations in educating their members in choosing national and local leaders. The group also reommended that the religious organizations/leaders should refrain from endorsing candidates to their members/followers during elections.
Research Paper (Mgt 199 - Management Research) -- Iloilo City : University of the Philippines in the Visayas, College of Management, March 23, 2001